Anti inflammatory properties and safety of green synthesized metal and metal oxide nanoparticles: A review article - Ream Nayal; Diana Mejjo; Mohammad Yaser Abajy (Elsevier, 2024)
NSAIDs, glucocorticoids, aminosalicylates, and immunosuppressants are nowadays the most commonly used anti-inflammatory medicines, although they have cosiderable side effects. Nanoparticles (NPs), notably metallic NPs, have gained appeal in the development of safer anti-inflammatory drugs. Because conventional NP synthesis methods are limited by environmentally unfriendly chemicals and high energy consumption, alternative green synthesis of metallic and metal oxide NPs, including plant-mediated synthesis, has piqued the interest of researchers due to phytochemicals that can reduce metal precursors and stabilize the generated NPs. This method is an eco-friendly, non-toxic, and cost-effective. This review aimed to highlight studies concerningthe anti-inflammatory activity of different plant-mediated green synthesis of metal and metal oxide nanoparticles with anti-inflammatory properties covering papers since 2017. According to the findings, the majority of the NPs tested were AgNPs. Noticeably, few investigations were conducted to assess the stability and safety of these NPs. Remarkably, someNPs exert more anti-inflammatory activity than plant extract itself and the standard. Some anti-inflammatory tests were limited to in vitro testing. Obviously, there is a lack of information regarding the safety issues of these NPs and the determination of their active doses. Thus, further invitro and invivo pharmacological and toxicological studiesare required for these metal and metal oxide NPs to identify medicinal uses and avoid unintended adverse consequences. It is also urgent to test the stability of these NPs in various dosage forms after determining the optimal active dose.